Results of lumbar interbody fusion in elderly patients with lumbar spinal stenosis associated with cauda equina syndrome - A. A. Kalinin; D. V. Hozeev; V. Yu. Goloborodko; Yu. Ya. Pestryakov; V. V. Shepelev; E. E. Satardinova; V. A. Byvaltsev (Инновационная медицина Кубани)
Background: Currently, there are no clear recommendations on the timing of surgical intervention for the slow development of cauda equina syndrome (CES) against the background of lumbar spinal stenosis (LSS) at the lumbar level in elderly patients. The information on the long-term effectiveness of decompressive and stabilizing interventions (DSI) in the lumbar spine in this pathology is also limited.Objective: To conduct a comparative analysis of the results of surgical treatment of elderly patients with LSS associated with CES after open and low-traumatic DSI.Material and methods: The retrospective study included 37 patients operated on between 2000 and 2020 for CES caused by LSS. Two groups were distinguished: in the first group (n = 17), an open DSI was performed with the median approach, in the second group (n = 20) a low-traumatic DSI was performed according to the author’s method. Technical features of interventions and specificity of the postoperative period, preoperative instrumental data, clinical parameters in dynamics, and complications were compared.Results: In a comparative analysis in the group of patients operated on with author’s low-traumatic DSI, smaller parameters were registered: the duration of the operation (p = 0.02), the blood loss (p = 0.003), the duration of inpatient treatment (p = 0.002), and the postoperative need for opioid analgesics (p < 0.05). In catamnesis, statistically significantly better clinical parameters of bladder sphincter control (p = 0.02) and motor function recovery (p = 0.01), Oswestry Disability Index (ODI) (p = 0.03) and the Short Form-36 (SF-36) (p = 0.01) were observed in patients of the group II, compared with the group I. A greater number of complications were noticed in the group of open DSI (p = 0.003), with a comparable frequency of reoperations in the follow-up period (p = 0.79).Conclusion: In elderly patients with CES-associated LSS, the advantages of the author’s low-traumatic DSI in comparison with open DSI were established of less blood loss and duration of hospitalization, low need for postoperative analgesia, the minimum number of complications, and the dynamics of neurological symptoms, better recovery of ODI and SF-36 in catamnesis.